Brandalism and social protest: interactions and digital identities around vandal advertising - Guerra, José Miguel (2022)
Brandalism or subvertising refers to the advertising discourse that adopts anti-consumerism positions to make a social critique. Considering the context of social protest during the pandemic, we investigated discourses forms of brandalism through the digital platform Facebook. Therefore, this article analyzes the interactions of political consumers in relation to the themes of brandalism of the Malditos Publicistas account on Facebook (@Malditospublicistas) in the context of the protests against the government of Manuel Merino during 2020, in Peru. Based on the case study from a sociosemiotic perspective, we identified thematic axes comprised in the ethical-political relationship of the brandalist discourse, as well as digital interactions that we categorized as "lurkers", "spectators", "activists", and "publishers". The results indicate a greater participation of lurkers and publishers reactive to ethical discourses than activists who favor the political agency of the discourse.